Methods of development and ensuring entrepreneurship competitiveness in the sphere of tourism - M. A. Yakhjyaev; I. M. Bogdanova (Путеводитель предпринимателя, 2020)
In the publication the methodical features of assessment of development of tourism used in practical activities are revealed. Application of an author’s technique of assessment and ensuring competitiveness of entrepreneurship in the sphere of tourism taking into account specifics of the Republic of Dagestan is proved and the potential of its use for updating of state programs of development of tourism is realized.